ANALISIS SPASIAL TINGKAT SEBARAN PERAMBAHAN KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO - Mangil, Wahyu Rizky S; Akhbar, Akhbar; Muis, Hasriani; Arianingsih, Ida; Misrah, Misrah (Universitas Tadulako, 2020)
High population growth has become an important factor in the utilization of forest and land resources. Along with the increase in population growth, the fulfillment of life necessities is also increasing, this condition has directly or indirectly been a causal factor and a trigger factor for pressure on forest and land resources. Identification of encroachment area distribution is needed to formulate strategies for handling and preventing encroachment, so that prevention and monitoring activities can run more effectively and efficiently. Educational forest is an educational facility that aims to support and improve quality. Very important information is needed in the context of educational forest management. Based on data from the Environmental Agency of Donggala Regency (2013), the forest area in Donggala Regency is 284,101 Ha. However, the area of forest cover continues to decline. This is partly due to the activities of rural communities around the forest, especially in the Tadulako University Education Forest area. The method used in this study is the scoring and overlay using ArcGis 10.0 software, as well as the field survey method to obtain coordinates. Based on the results of research conducted in the Tadulako University Forest Education area, it is known that most areas in educational forest areas tend to be prone to encroachment activities. The results of the analysis showed that the area included in the category of high hazard vulnerability was 433.08 ha or 23.88%, medium encroachment level was 839.56 ha or 46.30%, and the vulnerability level lowÂ was 540.59 ha or 29.81%.Keywords : Encroachment, Educational Forest, Scoring, Overlays, Encroachment distribution map